Presentation of a new system in longitudinal tomography (micro layer tomography) - Navabpoor, Mojtaba; Navvabpour, Naeima (Archives of Advances in Biosciences, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>Tomography or planigraphy is an X-Ray imaging system for preserving a certain plane of a radiography object by diffusing the other planes; however, the wanted plane does not obtain an optimum sharpness. Meanwhile, relatively nearer points to the rotating axes fixed point have lesser linear velocity than those of lying further from fixed point, consequently, Tomographic Bluring (obscuring) occur gradually, that gives rise the wanted plane to be somehow blurred that is known as "tomographic blurring", hence the clinical value of the image is diminished.This innovation could be an approach to improve current tomography systems by increasing image resolution and deep resolution and cost reduction. Micro layer tomography with benefit of fast X –Ray rotating velocity without tube movement has been designed to make images with deep resolution of millimeter fraction whilst, there is no need of digital images reconstruction instruments that allows statistical errors to fall off about zero, and high resolution images could be prepared in all planes (coronal, sagital and cross sectional. Likewise, the patient treatment and the system maintenance cost are much less by many degrees compared with those in CT scan and MRI. In this system with increasing evolution, quick operation is highly exception, hence the tomographic slices could be prepared in about less than 0.02 second. The laboratory samples of this system have been a unique result for proving the new device preference.